Training and capacity building on the effects of climate change on health: a need to up-scaling - Chambaud, L (European journal of public health, 2024)
The need to develop training on the effects of climate change on health is obvious, as the awareness on this topic is growing but the knowledge is not enough disseminated. ASPHER has taken several initiatives to address this subject. Among them, three activities deserve to be highlighted: in cooperation with the GCCHE, we have set up an intensive online course with a great success (nearly 1.000 participants in each of the 10 sessions). With the same partner we have conducted a survey in all SPHs members of our network, to be able to map training activities in the European Region and follow their development. We also work with the European Observatory on climate change and health to reinforce capacity building at European level. But this is not enough and we have to go faster and further in several directions: by linking more closely multidisciplinary research and training, as knowledge is evolving quickly; by developing specific training for all public health trainees. This is why we need to incorporate this topic in public health core curriculum; by having some modules tailored to different publics: public health professionals, health professionals, but also local, national and European decision-makers and stakeholders. To conduct these activities, we have to reinforce our different partnerships and create a powerful alliance at the European level.